Combined catalytic strategies applied to in-office tooth bleaching: whitening efficacy, cytotoxicity, and gene expression of human dental pulp cells in a 3D culture model - de Oliveira Ribeiro, Rafael Antonio [UNESP]; Peruchi, Victória [UNESP]; Sores, Igor Paulino Mendes [UNESP]; Mon, Filipe Koon Wu [UNESP]; Soares, Diana Gabriela; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (My University, 2024)
Objectives: To evaluate the feasibility of using a 3D model with human dental pulp cells (HDPCs) to compare bleaching therapies and assess whether coating enamel with a nanofiber scaffold (NS) and polymeric catalyst primer (PCP), combined with violet LED (LEDv) irradiation, enhances bleaching efficacy (BE) and reduces cytotoxicity (CT). Materials and methods: After using NS + PCP to cover enamel of enamel/dentin discs adapted to artificial pulp chambers containing 3D culture with HDPCs, a bleaching gel with 35%H2O2 was applied and then irradiated with LEDv. The following groups were established (n = 8): NC - no treatment; PC– 35%H2O2 for 45 min, and EXP: NS + PCP + 35%H2O2 + LEDv for 15 min. The study evaluated BE (ΔE00 and ΔWID), CT (alamarBlue), and HDPCs gene modulation (TNF, IL1B, PTGS2, IL8, IL6, PPRAG, HMOX1, DSPP, DMP1, SPP1, BGLAP, and ALPL; RTqPCR). Results: BE showed no significant difference between PC and EXP (p > 0.05). EXP had lower oxidative stress, higher cell viability, reduced inflammatory marker expression, and increased mineralization marker expression compared to PC (p < 0.05). Conclusion: The 3D model using HDPCs effectively compared bleaching protocols. Coating enamel with NS + PCP and applying violet LED (LEDv) reduced bleaching time from 45 to 15 min while lowering cytotoxicity compared to conventional in-office treatments. Clinical relevance: This study shows that a 3D model with human dental pulp cells (HDPCs) effectively compares tooth bleaching protocols. The combination of a nanofiber scaffold with violet LED (LEDv) reduces bleaching time, as well as minimizes cytotoxicity and inflammation, offering a safer alternative to conventional treatments.
Keywords: 3D culture; Catalysis; Dental pulp; Gene expression; Tooth bleaching